ANALISA DISTRIBUSI PANAS PADA ALAT PENGERING RUMPUT LAUT (STUDI KASUS PADA ALAT PENGERING RUMPUT LAUT DI SITUBONDO) - Widodo, Basuki (MATEMATIKA, 2005)
In Situbondo, seaweed drying is currently conducted tradityonally. This process produces low quality seaweeds. An alternative way to cope this problem is to develop an hybrid power drying equipment utilizing heat energy from fuel and solar energy. The result of this drying depends on heat distribution. To understand the heat dispersion, one need to analyse temperature distribution in the drying equipment, in particular in the drying plate. Therefore, a model distribution on plate is developed when the heat inÂ from solar and stove. The model is solved using Finite Different Method. The solution will be formulating to the central, side and corner of the plate. Computation with Matlab will be compared with the result of complements Fluent 6.0 software. The result show that the heat transfer occurs from one area in the plate to others areas due to temperature difference. The profile of the temperature distribution decreases and dispers vertically and horizontally to the edge and the bottom of the plate.